Isotopic (δ15N and δ13C) profiles in dentine indicate sex differences and individual variability in resource use among narwhals (Monodon monoceros). Issue 3 (18th March 2022) - Zhao, Shu‐Ting; Davoren, Gail K.; Matthews, Cory J. D.; Ferguson, Steven H.; Watt, Cortney A.
Abstract: While the impact of ecological changes on Arctic marine mammals remains largely unknown, quantifying variability in resource use among conspecifics can serve as an indication of adaptive plasticity and help assess species vulnerability to climate‐induced changes. We measured within‐tooth δ 15 N and δ 13 C profiles of narwhals ( Monodon monoceros ) sampled 35 years apart from Baffin Bay, Nunavut, Canada, to evaluate intrapopulation variation in narwhal resource use. Narwhal dentine δ 15 N and δ 13 C were lower post‐1983 ( n = 7) by 0.83‰ and 0.52‰, respectively, compared to pre‐1983 ( n = 13), but isotopic niche breadth increased from 0.95‰ 2 to 1.12‰ 2 . Between sexes, the isotopic niche of males expanded from pre‐1983 to post‐1983 while that of females decreased, which may indicate increased flexibility in resource use for males and the opposite for females. Additional isotopic variation among narwhals ( n = 23) suggests individual differences in diet composition and/or foraging location during both periods. Individual isotopic niches ranged between 0.08‰ 2 and 2.27‰ 2, where a larger isotopic niche likely indicates more variable foraging strategies over time. Narwhal as a species is considered vulnerable to ecosystem change; however, the variability in resource use between sexes and among individuals suggests narwhals may vary in their adaptability to changing Arctic conditions.